Social-Economic Changes of Society Post-September 30, 2009 Earthquake in Pariaman City - Dedi Hermon; Aprizon Putra; Erianjoni Erianjoni; Olivia Oktorie (Science and Environmental Journal for Postgraduate, 2020)
The aims of this study are to 1) describe the forms of changes in socio-economic life after the earthquake disaster on September 30, 2009; and 2) Explaining the impact of change on the interaction of the society of Pariaman City. Data was collected using observation, interviews, and documentation. To test the validity of the data, the researcher triangulated the data. The research informants were the victims of the September 30, 2009 earthquake, society leaders, sub-districts, and city governments. The technique of selecting informants using snowball sampling. Data analysis of this research was carried out using an interactive model developed by Matthew Miles and Huberman (1992). The findings of this study indicate the changes in the socio-economic life of the society after the September 30, 2009 earthquake marked by the increasingly heterogeneous social life such as the formation of new groups in society, the diversity of livelihoods. The impact of the change causes society to become more individualistic, social relations are more tenuous and more selfish and the society is dependent on obtaining earthquake relief funds.